2012
DOI: 10.1200/jco.2012.30.18_suppl.lba3500
|View full text |Cite
|
Sign up to set email alerts
|

Bevacizumab (Bev) with or without erlotinib as maintenance therapy, following induction first-line chemotherapy plus Bev, in patients (pts) with metastatic colorectal cancer (mCRC): Efficacy and safety results of the International GERCOR DREAM phase III trial.

Abstract: LBA3500^ Background: Therapy targeting VEGF or EGFR demonstrated clinical activity in combination with chemotherapy (CT) in mCRC but monoclonal antibodies cannot be associated. The DREAM trial compares a maintenance therapy (MT) with bev +/- EGFR tyrosine kinase inhibitor erlotinib (E) after a first-line Bev-based induction therapy (IT) in pts with mCRC. Methods: Pts with previously untreated and unresectable mCRC were eligible. After a Bev-based IT with FOLFOX or XELOX or FOLFIRI, pts without disease progres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…The development of epidermal growth factor receptor tyrosine kinase inhibitors (EGFR TKI) in the treatment of metastatic colorectal cancer (mCRC) has taken a new turn with the recent reports on the DREAM and the DUX studies, which showed that erlotinib may play a role when combined with either bevacizumab or cetuximab in the palliative treatment of mCRC. Studies in preclinical models of CRC have demonstrated an additive to synergistic effect on growth inhibition when an EGFR TKI is combined with chemotherapy .…”
Section: Introductionmentioning
confidence: 99%
“…The development of epidermal growth factor receptor tyrosine kinase inhibitors (EGFR TKI) in the treatment of metastatic colorectal cancer (mCRC) has taken a new turn with the recent reports on the DREAM and the DUX studies, which showed that erlotinib may play a role when combined with either bevacizumab or cetuximab in the palliative treatment of mCRC. Studies in preclinical models of CRC have demonstrated an additive to synergistic effect on growth inhibition when an EGFR TKI is combined with chemotherapy .…”
Section: Introductionmentioning
confidence: 99%
“…A number of clinical studies (18,19) support the use of capecitabine as maintenance therapy, as it has been shown to prolong PFS, but provides no OS benefit. It is recommended that such patients receive a local, minimally invasive treatment to achieve TFS.…”
Section: Discussionmentioning
confidence: 99%
“…The much higher pathologic response rate seen in this trial suggests that dual targeting of the VEGF and EGFR pathways may have a synergistic effect on chemoradiation. There is prior evidence supporting the combination of bevacizumab and erlotinib in colorectal cancer; a randomized trial has shown that maintenance therapy with bevacizumab and erlotinib improves progression-free survival, compared to maintenance therapy with bevacizumab alone in patients with metastatic colorectal cancer 24 . The role of erlotinib appeared to be independent of KRAS status in that trial 25 .…”
Section: Discussionmentioning
confidence: 99%